2022
DOI: 10.1088/1755-1315/1063/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

Situation analysis of fulfillment of beef needs and opportunities for beef cattle partnership

Abstract: Around 30-40% of Indonesia’s domestic beef needs depend on imports, especially for Jakarta and its surroundings. For this reason, it is necessary to develop cattle farming and improve various sectors so that Indonesia does not depend on imports. Situational analysis research was conducted to determine the actual condition of cattle farming and prospects for the model of people’s beef cattle partnerships financing. The research was conducted by analyzing literature and applying survey techniques with a direct i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A more in-depth analysis showed that the highest cost of procurement is the purchase of BX feeder cattle from Australia. The research result from Suhendar and Sukardi (2022) showed since August 2020, the price of feeder cattle from Australia has increased to US$ 3.7 per kg from previously US$ 3 per kg, meaning that the landing cost will reach Rp. 52,000 per kg of live cattle.…”
Section: Procurement Of Bx Cattlementioning
confidence: 99%
“…A more in-depth analysis showed that the highest cost of procurement is the purchase of BX feeder cattle from Australia. The research result from Suhendar and Sukardi (2022) showed since August 2020, the price of feeder cattle from Australia has increased to US$ 3.7 per kg from previously US$ 3 per kg, meaning that the landing cost will reach Rp. 52,000 per kg of live cattle.…”
Section: Procurement Of Bx Cattlementioning
confidence: 99%
“…While sensors and controllers don't need a lot of bandwidth, they do need very little delay and very little energy to guarantee longer battery life, particularly in situations where there are several devices involved [23]. ZigBee technology makes it possible to deploy trustworthy wireless networks widely while providing simple and affordable solutions.…”
Section: The Zigbee Technologymentioning
confidence: 99%
“…ZigBee technology makes it possible to deploy trustworthy wireless networks widely while providing simple and affordable solutions. It is appropriate for the economical support of resilient mesh networking technologies since it enables devices to run for prolonged periods of time on reasonably priced primary batteries [23].…”
Section: The Zigbee Technologymentioning
confidence: 99%
See 1 more Smart Citation